The Role of Insulin-Regulated Aminopeptidase in MHC Class I Antigen Presentation - Van Endert, Peter M.; Saveanu, Loredana (Frontiers in Immunology, 2012)
Production of MHC I ligands from antigenic proteins generally requires multiple proteolytic events. While the proteolytic steps required for antigen processing in the endogenous pathway are clearly established, persisting gaps of knowledge regarding putative cross-presentation compartments have made it difficult to map the precise proteolytic events required for generation of cross-presented antigens. It is only in the past decade that the importance of aminoterminal trimming as the final step in the endogenous presentation pathway has been recognized and that the corresponding enzymes have been described. This review focuses on the aminoterminal trimming of exogenous cross-presented peptides, with particular emphasis on the identification of Insulin Responsive AminoPeptidase (IRAP) as the principal trimming aminopeptidase in endosomes and phagosomes.